Fetal Sex Selection: An Appraisal of Ethicality Debate in Contempoaray Islamic Family Law - Haneef, Haneef Sayed Sikandar; Abdul Razak, Mohd Abbas (AL-MASHALIH (Journal of Islamic Law), 2018)
Assisted Reproductive Technology continues to create numerous possibilities to improve health and overcome serility. In consequence, in term of socio-cultural implciations, it is poised to create new life styles by challenging a plethora of traditional beliefs and norms about human procreation including the sex formation of a baby in natural way. In this context, the use of Intra-Uterine Insemination(IUI) for sex selection and the invention of preimplantation genetic diagnostic(PGD through In vitro Fertilization(IVT have proven revolutionary not only to obviate the birth of children with fatal sex linked diseases but to help people to predetermine the sex of their babies. As to how contemporary Muslim jurists have endeavoured to reconncile ethic-legal norms of Islamic view of human procreation with such technological intervention in the process of human procreation, the discourse in Sunni Islamic law tends to present some ethical dilemmas. It is candidly clear from a host of ethical queries which ethicians raise about ethicality of sexing from larger Shari`ah perspective. Accordingly, this paper by applying qualitative method of analysis concludes that adoption of a flux legalistic view on fetal sex selection is incosisttent with the divine purpose of human procreation except if warranted by restrictively defined medical reason.